2022
DOI: 10.5116/ijme.61dd.7764
|View full text |Cite
|
Sign up to set email alerts
|

Clinical teachers’ professional identity formation: an exploratory study using the 4S transition framework

Abstract: Objectives:The aim of this study was to explore factors that may influence the formation of professional identity in clinical teachers, specifically during the transition period from practitioner to teacher. Methods: This was a descriptive qualitative study. We used Schlossberg's 4S framework to explore influential factors comprised of the following: situation, self, support, and strategies. This study was conducted in teaching hospitals of a relatively new private medical school in Bali, a province in Indones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…have identified 12 subthemes influencing the development of PIF in clinical teachers, which included self-efficacy, motivation, teaching impact, institutional support, peer support, students’ participation in learning, and teacher training. [ 14 ] The themes and subthemes generated in the current study are very much in agreement with the subthemes generated in the study conducted by Sueningrum et al .…”
Section: Discussionsupporting
confidence: 91%
“…have identified 12 subthemes influencing the development of PIF in clinical teachers, which included self-efficacy, motivation, teaching impact, institutional support, peer support, students’ participation in learning, and teacher training. [ 14 ] The themes and subthemes generated in the current study are very much in agreement with the subthemes generated in the study conducted by Sueningrum et al .…”
Section: Discussionsupporting
confidence: 91%
“…35,36 However, it has since been shown to have wider applications, including clinical practice, social work, occupational therapy, leadership, education and career development. 37 Adopting a midrange theoretical approach 31 focusing on the practical application of the ideas rather than the philosophical aspects, recent research into transition theory has shown that it can be usefully applied to the study of the process in which healthcare educators move from a primary professional identity (such as nurse, dentist or doctor) to a new, integrated identity where the educator and clinical/academic identities are held in satisfactory equipoise. 11,38,39 The process of moving from primary professional identity, through a series of changes, towards a more stable integrated self-identity may not be linear or involve significant stress to the individual; and it is certainly not permanent, 40 but it does involve a temporal progression against which healthcare educator career trajectories can be theorised.…”
Section: Transition Theorymentioning
confidence: 99%
“…Transition theory emerged in the 1970s as a new conceptual field that attempted to integrate, explore and develop previous approaches to understanding and assisting psychosocial adjustment to grief and loss 35,36 . However, it has since been shown to have wider applications, including clinical practice, social work, occupational therapy, leadership, education and career development 37 . Adopting a mid‐range theoretical approach 31 focusing on the practical application of the ideas rather than the philosophical aspects, recent research into transition theory has shown that it can be usefully applied to the study of the process in which healthcare educators move from a primary professional identity (such as nurse, dentist or doctor) to a new, integrated identity where the educator and clinical/academic identities are held in satisfactory equipoise 11,38,39 .…”
Section: Transition Theorymentioning
confidence: 99%
“…The study suggests that this identity shift is a dynamic process influenced by personal beliefs, prior learning experiences, teaching practice, and the institutional exam-oriented culture. Furthermore, another which adapted the same 4S transition framework investigated the factors influencing the formation of professional identity in clinical teachers during the transition from practitioner to teacher (Caza & Creary, 2016;Sueningrum et al, 2022). The study found that situation, self, support, and strategies were influential.…”
Section: Introductionmentioning
confidence: 99%